i'm going to take a wild guess and say this is problem #32... am i right???

f + g = (1+x)^(1/2) + (1-x)^(1/2)

that's it!!!! why?? we cannot add radicals.

f - g = (1+x)^(1/2) - (1-x)^(1/2)

that's it!!! why?? we cannot subtract radicals.

fg = (1+x)^(1/2) * (1-x)^(1/2)

use the property (ab)^(1/2) = (a)^(1/2) * (b)^(1/2)

[(1+x)(1-x)]^(1/2)

(1-x^2)^(1/2)

f/g = (1+x)^(1/2) / (1-x)^(1/2)

use the property: (a/b)^(1/2) = (a)^(1/2) / (b)^(1/2)

[(1+x) / (1-x)]^(1/2)

that's it buddy!!

]]>The problem tells me to add, subtract, multiply and divide two given functions, but I am not sure how to continue since they are square roots.

Here are the functions:

f(x) = sq.root(1+x) and g(x) = sq.root(1-x)

Find: f+g, f-g, fg, and f/g

Any help is much appreciated.

]]>